Rethinking Dating and SEXUAL Violence Prevention for Youth During the Pandemic: Examining Program Feasibility and Acceptability - Segura, Anna (Journal of interpersonal violence, 2023)
Sexual and dating violence (SDV) is a social and health but preventable public issue. Most evidence-based prevention programs have been evaluated using an in-person delivery mechanism. Project Dream, Own and Tell (DOT) is a 13- to 18-week SDV prevention program targeting youth from traditionally underserved communities in New York City that shifted from in-person to online delivery in response to social distancing requirements during the COVID-19 pandemic. The aim of the current study was to understand how youth perceive learning SDV prevention in an online environment (acceptability and feasibility of the online DOT program). A mixed methods triangulation design was used including responses to Ecological Momentary Assessments (n = 25), a brief post survey with Likert-scale items (n = 18), and semi-structured interviews with 12 participants. The sample comprised Latinx/Hispanic, Asian American, Arab American, and African American youth between the ages of 15 and 21 from urban communities. Youth indicated both strengths and challenges of the online format. Strengths included ease of fitting the program into their schedules, avoiding long commutes, and the potential to create a safe online space for participants to engage in sexual violence prevention discussions and thus, feel less exposed. Challenges included internet connectivity issues, difficulties in building trustworthy relationships with other participants when not sharing the same physical space, some characteristics of the program’s activities, and the lack of adequate space from which to attend the program (i.e., shared spaces). Findings suggest that synchronous online prevention program delivery is a feasible and acceptable strategy for engaging adolescents in relationship violence prevention.